A Critical Study on the Definitions of Children Literature - Sawaedi, A del; Shirmohammadi, Elahe (International Journal of Psychosocial Rehabilitation, 2020)
The present study is an endeavor to challenge the pre-existing definitions of children literature. The definitions are not inclusive as they have ignored the cultural, geographical, economic and familial differences so that it is imagined that every child with any background is able to utilize literary productions. However,considering the above difference reveals that according to the existent definitions, children literature doesn’t include all children and also all of them would not benefit from this literature in the same way. Moreover, based on the economic circumstances, some children cannot use literary works. So, this research claims that not being comprehensive, the existent definitions require revision. Also, it is an attempt to claim that the producer of literary works is not necessarily to be an adult and works produced by children should be regarded as children literature. In this regard, first of all, different definitions of literature and children literature will be discussed and then they will be criticized psychologically. The results present that the definitions are not inclusive and they are in need of analysis and reconsideration.